Jejunoileal Atresia A study of 60 cases in children welfare teaching hospital. - Khalaf, Ahmed A.; Al-Obaidy, Munthir A.; Khalaf, Kawthar F. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Congenital defects in continuity of the intestine are morphologically divided into either stenosis or atresia and constitute one of the most common causes of neonatal intestinal obstruction. Patients and methods: This is a prospective study for analyzing (60)neonates with jejunoileal atresia who were managed at Children Welfare Teaching Hospital in Baghdad over a three years peroid extending from 1st January 2004 to 1st January 2007.Results: Thirty six patients (60%) had jejunal atresia while ileal atresia was in(24) patients(40%).The most common type of jejunoileal atresia was type IIIa (38.3%) of the cases and the second was the type II (25%).The clinical presentation for jejunal atresia was mainly bilious vomiting and occurred in(100%)of the cases, while failure of passing meconium in the first day of life was the most common presentation in ileal atresia and occurred in (91.7%). Abdominal distention is more frequent in ileal atresia (87.5%) in comparism to (50%) in jejunal atresia. The number of males was (35) and the number of females was (25) and the male: female ratio is 1.4:1. The most common surgical complications were anastomotic leak and wound infection. There are several other factors contributing to the increased mortality rate such as delayed in diagnosis, associated anomalies, neonatal septicemia and aspiration pneumonia.Conclusion: Jejunal atresia most commonly presents with bilious vomiting while ileal atresia presents with abdominal distention and failure to pass meconium in first day of life. The most common type of the atresia in our study was type IIIa while type IV is the rarest. There are several surgical procedures used in the treatment of atresia but wide proximal resection and end to end anastomosis was the commonest procedure done.